Spatio-temporal variation in avian taxonomic, functional, and phylogenetic diversity and its relevance for conservation in a wetland ecosystem in Myanmar - Htay, Thazin; Røskaft, Eivin; Ringsby, Thor Harald; Ranke, Peter Sjolte (Biodiversity and conservation, 2023)
Wetland ecosystems host an extensive number of avian species and play therefore a key role in biodiversity conservation. However, avifauna in wetlands is severely impacted by the anthropogenic transformation of natural habitats into other land uses. Understanding how habitat changes influence avian community dynamics is crucial for effective management and conservation of bird habitats. Here, we assessed spatio-temporal variation in taxonomic, functional, and phylogenetic diversity, and assembly structures of the bird community in the Indawgyi Wetland Ecosystem in Myanmar. Bird surveys were seasonally conducted at 120 sample plots, which were equally distributed among four habitat types subject to different level of human influences (natural lake habitat, seasonally flooded grasslands, riparian forest, and agricultural land). Across habitat types, functional and phylogenetic diversity were the highest in the lake habitat, especially during the migration season, and the lowest in the cultivated habitat. Our results indicated over-dispersed functional and phylogenetic structures in the lake habitat, with clustered structures in the remaining habitats. Diversity of species important for conservation was also higher in the lake habitat and in areas far away from human disturbances. Spatial variation of bird community diversity suggests that conservation efforts in this ecosystem should concentrate more on the lake habitat and associated grassland habitats. Moreover, our results suggest the need for habitat restoration in riparian forests and increased sustainable agricultural practices in order to improve the contribution of these habitats to the diversity in the avifauna community. Our study highlighted the importance of integrating functional and phylogenetic dimensions into biodiversity analyses providing broader ecological insights for conservation.